2003
DOI: 10.1007/s10071-003-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of food types in zebra finches (Taenopygia guttata) is directed by demonstrator sex and feeding activity

Abstract: In this study we examined how social learning of feeding preferences by zebra finches was affected by the identity of different demonstrators. We presented adult zebra finches with two demonstrators, one male and one female, that exhibited different food choices, and we recorded their subsequent preference when given a choice between the two food types. Previously it was found that young zebra finches' patterns of social learning are affected by the sex of the individual demonstrating a feeding behaviour. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 9 publications
5
35
3
Order By: Relevance
“…Copying of food choices has also been demonstrated in zebra finches, Taeniopygia guttata, a species that forages in flocks on grass seed in Australia (Benskin et al, 2002;Katz and Lachlan, 2003; Experiment 2, Riebel et al, 2012). There is evidence that the extent of food copying varies among individuals (Rosa et al, 2012) and depends on experimental conditions (Guillette et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Copying of food choices has also been demonstrated in zebra finches, Taeniopygia guttata, a species that forages in flocks on grass seed in Australia (Benskin et al, 2002;Katz and Lachlan, 2003; Experiment 2, Riebel et al, 2012). There is evidence that the extent of food copying varies among individuals (Rosa et al, 2012) and depends on experimental conditions (Guillette et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…1). We followed the same procedure as in We first ran tests to determine if demonstrators behaved differently towards the 167 different coloured feeders and if male and female demonstrators behaved differently from one 168 another because previous research has indicated that feeding activity of demonstrators affects 169 observer behaviour (Katz and Lachlan, 2003). We conducted independent t-tests to test for 170 differences in the proportion of pecks delivered by the demonstrators to the feeder that 171 contained seed (1) when the demonstrated feeder was black or white, (2) when the 172 demonstrator was a male or a female, and (3) when the demonstrator/observer pair was 173 mixed-sex or same-sex.…”
mentioning
confidence: 99%
“…Learning is a cognitive process (Duncan & Petherick 1991) enabling animals to acquire information about the state of their immediate environment (Katz & Lachlan 2003) and their own individual state (Duncan & Petherick 1991). An inherent part of learning concerns information about food, in particular determining whether food is palatable and nontoxic, and thus safe to consume (Galef & Clark 1971), and the location of this food in time and space (Ostfeld 1985).…”
mentioning
confidence: 99%
“…Alternatively, group living may promote social learning, which involves learning about the environment through the observation of (Heyes 1993) and interaction with (Katz & Lachlan 2003) conspecifics, or the products of their behaviours (Heyes 1994). This may reduce the costs often associated with individual learning (Zentall 2006).…”
mentioning
confidence: 99%